2003
DOI: 10.1161/01.str.0000080677.24419.88
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic but Not Delayed Administration of Simvastatin Protects Against Long-Lasting Cognitive and Morphological Consequences of Neonatal Hypoxic-Ischemic Brain Injury, Reduces Interleukin-1β and Tumor Necrosis Factor-α mRNA Induction, and Does Not Affect Endothelial Nitric Oxide Synthase Expression

Abstract: Background and Purpose-Prophylactic administration of simvastatin has been shown to protect against brain damage and its long-lasting behavioral consequences in neonatal rats. To establish the drug treatment window, we evaluated the effectiveness of simvastatin administered at different intervals before and after stroke. Furthermore, we determined whether simvastatin affected endothelial nitric oxide synthase (eNOS) or inflammatory cytokines in brain tissue or cholesterol levels in serum. Methods-On postnatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 28 publications
2
50
1
Order By: Relevance
“…However, studies in postnatal rats subjected to hypoxia-ischemia showed that prophylactic administration of simvastatin reduced brain injury and improved functional recovery and that this prophylactic effect was associated with a reduction in cytokine expression but did not affect eNOS expression. 20 In parallel, our data demonstrate that administration of atorvastatin after stroke extended the therapeutic window of rht-PA by enhancement of cerebral microvascular patency and integrity, primarily by decreasing thrombosis. Combination treatment did not increase eNOS levels, and blocking NOS activity with the NOS inhibitor L-NAME did not abolish the beneficial effects of combination treatment on stroke.…”
Section: Discussionsupporting
confidence: 60%
“…However, studies in postnatal rats subjected to hypoxia-ischemia showed that prophylactic administration of simvastatin reduced brain injury and improved functional recovery and that this prophylactic effect was associated with a reduction in cytokine expression but did not affect eNOS expression. 20 In parallel, our data demonstrate that administration of atorvastatin after stroke extended the therapeutic window of rht-PA by enhancement of cerebral microvascular patency and integrity, primarily by decreasing thrombosis. Combination treatment did not increase eNOS levels, and blocking NOS activity with the NOS inhibitor L-NAME did not abolish the beneficial effects of combination treatment on stroke.…”
Section: Discussionsupporting
confidence: 60%
“…Total RNA was prepared by guanidium thiocyanate denaturation from frozen kidney collected from vehicle-and valsartan (10 mg/kg/day)-treated rats sacrificed after 6 weeks of dietary treatment. The expression of MCP-1, TGF-␤1, and IL-1␤ was measured by semi-quantitative RT-PCR (Balduini et al, 2003). GAPDH was amplified as a standard.…”
Section: Anti-inflammatory Effects Of Valsartan In Shrsp 991mentioning
confidence: 99%
“…Positive cells were counted using the NIH-Image software in three separate fields of the cerebral cortex in slices cut at the level A 3750 of the Koning and Klippel stereotaxic atlas. 30 Five animals for each group were analyzed. Assessment of brain damage.…”
mentioning
confidence: 99%